Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. III : Leo III to Nicephorus III, 717-1081. Pt. 2 : Basil I to Nicephorus III, 867-1081. - Grierson, Philip. (Washington)
viii, s. [473]-887, s. xxx-lxx res.